2018
DOI: 10.2298/pac1803262r
|View full text |Cite
|
Sign up to set email alerts
|

The luminescence properties of yttria based phosphors and study of YBO3 formation via H3BO3 addition

Abstract: In this paper, Y 2 O 3 :Eu 3+ nano-phosphor was synthesized through the facile solid-state method and influence of H 3 BO 3 addition to the prepared Y 2 O 3 :Eu 3+ powder was investigated. The consumption of boric acid resulted in the formation of YBO 3 by changing the crystal structure from cubic to hexagonal. Noteworthy, through the use of specific quantities of H 3 BO 3 (medium amount), Y 3 BO 6 impurity with the monoclinic crystal structure and the space group C2/m was formed. FESEM observations showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…It was confirmed that the high-energy ball milling process reduced the particle size and improved the asymmetric ratio or color purity [14]. It was found that the addition of H 3 BO 3 not only increases the particle size from approximately 80 nm to 1 µm, but also changes the crystal structure from cubic to hexagonal (belonging to YBO 3 ) [15,16].…”
Section: H3bo3 → Hbo2 + H2o↑mentioning
confidence: 79%
See 1 more Smart Citation
“…It was confirmed that the high-energy ball milling process reduced the particle size and improved the asymmetric ratio or color purity [14]. It was found that the addition of H 3 BO 3 not only increases the particle size from approximately 80 nm to 1 µm, but also changes the crystal structure from cubic to hexagonal (belonging to YBO 3 ) [15,16].…”
Section: H3bo3 → Hbo2 + H2o↑mentioning
confidence: 79%
“…The slight broadening indicates the presence of no molecular water in the form of structure-forming OH groups. The band at 676 cm −1 is assigned to vibrations of the [BO 3 ] 3− structural group, the B-O-B bridge, or to vibrations of the atoms that form [B(O, OH) 4 ] tetrahedrons [14,15]. The band at 1194 cm −1 was probably caused by vibrations of atoms in the -O-B< bond in the structure of orthoboric acid.…”
Section: Structural Characterizationmentioning
confidence: 99%
“…So, they provide a symmetry center resulting in a strong 5 D0− 7 F1 transition [7]. Also, the addition of boric acid leads to changes in the crystal structure from cubic to hexagonal (belonging to YBO3) [8].…”
Section: Introductionmentioning
confidence: 99%